أثر برنامج تأهيلي مقترح لتنمية القوة في العضلات العاملة على مفصل الكاحل بعد التعرض للالتواء الخارجي لدى الرياضيين الممارسين لألعاب القوى - ضويا رشا; علي محمد; الرضوان مي (Latakia University Journal -Medical Sciences Series, 2019)
هدفت الدراسة إلى تطوير برنامج من التمرينات العلاجية لتأهيل إصابة التواء مفصل الكاحل الخارجي، بالإضافة إلى معرفة تأثير البرنامج على قوة العضلات العاملة على مفصل الكاحل. أجريت الدراسة على عينة مكونة من (11) رياضياً مصاباً من الممارسين لألعاب القوى في اللاذقية، وقد استخدم الباحثون المنهج التجريبي لملائمته طبيعة البحث، باستخدام تمارين وأدوات متنوعة. طبق البرنامج لمدة (6) أسابيع بواقع (3) وحدات تأهيلية في الأسبوع وتراوح زمن الوحدة التأهيلية بين (60-70) دقيقة، أجريت بعدها الاختبارات البعدية والمعاملات الاحصائية، توصلت الدراسة إلى أنه للبرنامج التأهيلي تأثير إيجابي على قوة العضلات العاملة على مفصل الكاحل. The aim of the study was to develop a program of therapeutic exercises to qualify the injury of the external ankle sprain. In addition to know the impact of the program on strengthen muscles which basically working on the ankle joint. The program was applied on (11) injured athletes that practicing athletics of Lattakia. The researchers used the experimental method to suit the nature of the research, using various of exercises and tools. The period of the program was (6) weeks with (3) rehabilitation units per week. The qualifying unit time ranged between (60-70) minutes, Then the subsequent tests and statistical analysis were done to get the results. the results showed that the rehabilitation program has a positive effect on strengthen muscles which basically working on the ankle joint.